BRICS, middle-income countries (MICs), and global agrarian transformations: internal dynamics, regional trends, and international implications. Issue 1 (2nd January 2018) - Cousins, Ben; Borras, Saturnino M.; Sauer, Sérgio; Ye, Jingzhong
ABSTRACT: The BRICS (Brazil, Russia, India, China, and South Africa) countries are emerging as key sites of agricultural commodity production, distribution, circulation, and consumption, contributing to major shifts in the character of regional and global agro-food systems. Their growing importance within the world food economy presents new challenges for scholars, activists, policy-makers, and development practitioners. The articles in this collection are located in their wider context, and the significance of their insights for a longer term research agenda within critical agrarian studies is explored. Four key themes are discussed: processes of agrarian change under way within BRICS countries; the role and impacts of BRICS countries in their respective regions; the rising importance of middle-income countries (MICs) within global and regional agro-food systems; and how the recent emergence of forms of populism, authoritarianism, and combinations of these two (i.e. 'authoritarian populism') is linked to the rise of the BRICS.